Role of Social Responsibility in Achieving Competitive Advantage: Case Study White Nile University – Kosti (2010 – 2021) - د. تهاني فارس عبيد يوسف; د. السماني محمد الغالي نور الدائم (White Nile Journal for Studies and Research, 2023)
The study aimed to identify the reality of application of social responsibility at the universities via raising stakeholders’ awareness as applied to the White Nile University (2017-2021), and to explore the role of social responsibility as an evaluative tool among the group of methods adopted by the university in the process of achieving a competitive advantage. The problem of the study is represented in the following main question: To what extent does the adoption of the social responsibility approach contribute to the achievement of competitive advantage? Thus, the basic hypothesis of the study is that there is a statistically significant relationship between social responsibility and the achievement competitive advantage. Depending on the problem and hypothesis of the study, the inductive, historical and analytical descriptive approach was used. A purposive sample of (100) individuals was selected from the population of the study. The study arrived at several findings; including the constant improvement of community services is the most appropriate in the enhancement of the competitive advantage of the university. The university has an obvious community service plan, and it uses various mass media to improve the community service. The study has also reached several recommendations, including that it is important for the university to conduct continuous educational programs to serve the community, holding training workshops to raise awareness among the beneficiaries and simplifying the regulations and laws for stakeholders so as to increase awareness and create a competitive advantage for the university. Keywords: Societal Responsibility, Competitive Advantage, Stakeholders, Social Service.